Protocol for an economic evaluation alongside a natural experiment to evaluate the impact of later trading hours for bars and clubs in the night-time economy in Scotland: The ELEPHANT study - Colin Angus; Emma McIntosh; Nurnabi Sheikh; Jim Lewsey; Niamh Fitzgerald; Carol Emslie; Houra Haghpanahan (BMJ Open)
Introduction The night-time economy comprises various sectors, including hospitality, transportation and entertainment, which generate substantial revenues and contribute to employment opportunities. Furthermore, the night-time economy provides spaces for leisure activities, cultural expression and social interaction. On-trade alcohol premises (places where consumers can buy and consume alcohol such as bars, pubs, clubs and restaurants) are a significant component of this night-time economy, functioning as focal points for socialising, entertainment and cultural events. However, when on-trade alcohol premises stay open later at night, this can be associated with negative public health impacts including increased alcohol consumption, intoxication, assaults, injuries and burden on public services including ambulance call outs, hospitalisations and increased impacts on criminal justice services. The evidence on the societal impact of policies to ‘later’ trading hours for bars and clubs in the night-time economy is limited. This protocol details the design of an economic evaluation of policy to later trading hours for bars and clubs in the night-time economy alongside the ELEPHANT study (National Institute for Health and Care Research (NIHR) Public Health Research, ref:129885).Methods and analysis The research design is an economic evaluation alongside a natural experiment within the ELEPHANT study carried out in Glasgow and Aberdeen. The economic evaluation has been designed to identify, measure and value prospective resource impacts and outcomes to assess the costs and consequences of local policy changes regarding late night trading hours for bars and clubs. A number of economic evaluation frameworks will be employed. A cost-effectiveness analysis (CEA) is appropriate for assessing the effectiveness of complex interventions when the impacts of policy are measured in natural units. Therefore, a CEA will be conducted for the primary consequence, alcohol-related ambulance call-outs, using a health service sector perspective. Since this outcome is essentially a cost, the CEA will also be reported as a cost-analysis. A cost-consequence analysis will also be performed for the primary and secondary consequences including all ambulance call-outs and reported crimes to evaluate the full economic impacts of later trading hours for bars and clubs in the night-time economy. The analysis will be conducted from a wider societal perspective, including health sector, criminal justice system, business and third sector perspectives and will be in line with the recent National Institute for Health and Care Excellence guidance and recommendations.Ethics and dissemination The economic evaluation of the ELEPHANT study will be conducted using secondary data. Thus, no ethical approval is required for this economic evaluation. However, ethical approval for the ELEPHANT study has been granted from the University of Stirling’s General Research Ethics Committee, and prior consent has also been obtained from the participants, if involved. The results of this study will be disseminated through peer-reviewed publications in journals and national and international conferences.